Edukasi Penggunaan Obat Melalui Kegiatan DAGUSIBU pada Siswa SMK 1 Muhammadiyah Samarinda - Alya Indriyati Wahyono; Finasti Ayu Pararak; Widya Andriyani; Fika Aryati (Jurnal Pelayanan dan Pengabdian Kesehatan untuk Masyarakat, 2026)
The practice of self-medication among adolescents continues to increase along with the transparency of information. However, a lack of understanding regarding proper medication management procedures risks triggering health problems and environmental pollution. This community service activity aims to increase the knowledge, awareness, and skills of SMK 1 Muhammadiyah Samarinda students in managing medications wisely through the DAGUSIBU (Get, Use, Store, and Dispose) program. This activity was carried out on May 18, 2026, involving 44 11th grade students using the Service Learning method. Evaluation of the program's success was measured using pre-test and post-test questionnaire instruments and supported by the use of educational media in the form of leaflets. The results of the initial measurement (pre-test) showed an average percentage of correct answers of 75.23%, indicating a basic understanding but still some misconceptions. After the interactive education, the post-test results showed a significant increase in understanding, with the average percentage of correct answers increasing to 94.32%. This health promotion activity was deemed highly effective in increasing understanding and health literacy related to proper medication management among students